Augmented paper: Developing relationships between digital content and paper - Luff, P.; Adams, G.; Bock, W.; Drazin, A.; Frohlich, D.M.; Heath, C.; Herdman, P.; King, H.; Linketscher, N.; Murphy, R.; Norrie, M.; Sellen, Abigail; et al. (Springer-Verlag, 2007)
Some of the most interesting developments within computer system design in recent years have emerged from an exploration of the ways everyday objects and artefacts can be augmented with computational resources. Often under the rubric of “ubiquitous computing”, research programmes in Europe, North America and Japan have directed substantial funding towards these initiatives, and leading industrial and academic research laboratories have developed a diverse range of ubiquitous computing “solutions”. These developments mark an important shift in system design, a shift that is having a corresponding impact on social science research. Surprisingly though, given the growing commitment to the ubiquitous and the tangible, there is a mundane, even humble artefact that pervades our ordinary lives that has received less attention than one might imagine. This artefact is paper.